Factors associated with the eruption of permanent teeth: A literature review - Corrêa, Suelen Castro Lavareda; Uchôa, Sue Ann Castro Lavareda; Corrêa, Davi Lavareda; Corrêa, Vania Castro (Seven Editora, 2024)
Variation in normal tooth eruption is a common occurrence, but significant deviations from established norms should prompt the clinician to perform diagnostic procedures to assess the patient's health and development. Disturbances in tooth eruption time may be symptoms of general conditions or indicative of altered physiology in craniofacial development. The objective of this literature review is to analyze the general factors that may influence the complex dynamics of permanent tooth eruption. While the eruption of permanent teeth is under significant genetic control, it is important to recognize other general factors that may play a crucial role in this biological process. Other general factors, such as gender, socioeconomic status, craniofacial morphology, and body composition, can interact in complex ways and influence tooth eruption. This approach seeks to provide a comprehensive understanding of the multiple variables involved in the eruption of permanent teeth. It is noteworthy that the most striking disorders in tooth emergence are often associated with systemic diseases and syndromes, underlining the need for an integrated approach that considers both oral health and the general condition of the body. DOI:https://doi.org/10.56238/sevened2023.007-076